How does inflation of food prices affect poverty? an analysis of the different households in the Philippines - Rosas, Kara Gianina D. (School of Economics, University of the Philippines Diliman, 2019)
The purpose of this study is to assess the vulnerability of households to food price shocks. Through using the Philippines as a case study, the researchers hope to determine how these shocks can cause food insecurity to different types of households. This paper measures the impact of actual food price changes from 2006 to 2009, the height of food inflation, on poverty in relation to their spatial location_ their classification as rural or urban and agricultural or non_agricultural in the Philippines. Through treating food prices and consumption patterns as heterogeneous, this study differs from conventional poverty analysis as actual prices are used. Merging the Family, Income and Expenditure Survey (FIES) with the Consumer Price Index dataset (CPI), the researchers were able to determine the effects on poverty measures, specifically, head count index, poverty gap and poverty severity. This study finds that, without other interventions, food inflation would lead to a significant increase in the number of households that fall below the poverty threshold except households whose source of income derives from agricultural activities. It also finds that much of the inflation during these years were fueled by the rise in staple food prices. Essentially, this paper aims to broaden the economic perspective of policymakers with regards to the heterogeneity of impacts of inflation through analyzing the deeper microeconomic levels of different subgroups. In hopes to find a solution to lessen the inequality gap of poverty between the rural and urban poor, this paper aims to aid policymakers to create projects targeted towards food insecurity.